Removal of volatile organic compounds from the coal-fired flue gas by adsorption on activated carbon. (15th June 2021) - Ma, Xiuwei; Yang, Linjun; Wu, Hao
Abstract: Removal of volatile organic compounds (VOCs) from coal-fired power plants is the key to reducing VOCs emissions to the atmosphere. Adsorption on activated carbon (AC) is considered to be an economical and environment-friendly method for removal of these low-concentration VOCs. The VOCs adsorption behaviors on AC were investigated under coal-fired flue gas environment by a fixed-bed reactor. Investigations showed that adsorption capacity of the five aromatic compounds ranged from 12.3 to 52.7 mg/g at 120 °C. The lower concentrations and the higher adsorption temperature resulted in the lower VOCs adsorption capacity on AC. Physical adsorption accounted for a large proportion in VOCs removal. VOCs adsorption capacity was reduced by 20.1–26.9% when the SO2, water vapor, and fly ash coexisted. Competitive adsorption was present among the SO2, water vapor, and VOCs. SO2 and water vapor preferentially occupied the polar oxygen-containing groups, inhibiting the electron donor-acceptor interaction between VOCs and the functional groups. The stronger the VOCs polarity, the greater the inhibition. The fly ash adhered to the AC external surface and blocked the macropores on the surface, which not only reduced the VOCs adsorption capacity but also lowered the adsorption rate. Selecting AC with large micropore volume and increasing adsorption time are conducive to the VOCs removal. Graphical abstract: VOCs removal from the coal-fired flue gas. Image 1 Highlights: The differences of adsorption/desorption of aromatic compounds were studied. Physical adsorption still occupied a large proportion at MHT condition. Inhibition of SO2 and water vapor on VOCs adsorption was by occupying polar groups. Fly ash adhered to AC surface reduced the VOCs adsorption rate and capacity.